Design and analysis of onion peeler machine - Mohd Aizad Bin Shafiai (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Onion is the important cooking ingredients in the world of cook. Each type of onion have a slice of peel. The current of method to peel a onion is by a traditional method. There are have many effect when use a traditional method such as using by a hand and knife. By using this traditional method, the probability to injured such as sore eyes and hand pain are too high. beside that the process also take a long time if the user need to peel in the large quantities